2005
DOI: 10.1007/s00105-005-1010-x
|View full text |Cite
|
Sign up to set email alerts
|

Milben, Läuse und Flöhe

Abstract: Ectoparasitoses or epizoonoses are skin disorders caused by animal parasites living on the body surface. Worldwide they are among the most frequent dermatoses, particularly in infancy and childhood. Distinguishing between conditions caused by permanent and temporary ectoparasites is important for the course and the required therapy. Permanent ectoparasites, such as scabies mite and head louse, spend all their life in or on the skin and have to be killed on the patient with suitable acaricides or pediculicides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This method is time consuming, requires trained personnel, and is resource intensive. 7 Several authors 7,13 consider it as the gold standard for head lice diagnosis but fail to sub-stantiate this assumption with appropriate data. Mumcuoglu et al 4 found a 4-fold higher prevalence of active infestation after dry combing compared with visual inspection in children with a high intensity of infestation.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is time consuming, requires trained personnel, and is resource intensive. 7 Several authors 7,13 consider it as the gold standard for head lice diagnosis but fail to sub-stantiate this assumption with appropriate data. Mumcuoglu et al 4 found a 4-fold higher prevalence of active infestation after dry combing compared with visual inspection in children with a high intensity of infestation.…”
Section: Commentmentioning
confidence: 99%
“…5 In contrast to settings in the developing world in which a high intensity of infestation is the rule, in industrialized countries most children carry only a few lice. 6,12,13 In consequence, the optimal detection method should identify even a single louse and should have a high negative predictive value to exclude the possibility that individuals classified as negative for lice are actually false negative with the potential to spread the parasite. In this regard, wet combing is the only useful method if active infestation has to be ruled out.…”
Section: Commentmentioning
confidence: 99%